Productivity variation and its intersectoral spillovers: An analysis of Brazilian economy - Mariana Camarin Gazonato; Maria Aparecida Silva Oliveira (EconomiA, 2019)
The main purpose of this article is to analyze the capacity of Brazilian economy sectors to transfer their productivity gains over the productive chain from 2000 to 2009. Therefore, it has been used structural decomposition technique and a methodology that deals with the variation of labor productivity. The results of this article yield in the period under review are that the Services and not the Industry were the responsible for transmitting these increments of productivity. However, the power of transmission of productivity variation of the tertiary sector comes to be relatively low when compared to the ability of the Industry to transmit its productivity variations.
Keywords: C67; O14; O40; 330; Productivity gains; Power of transmission; Intersectoral spillovers; Service economy; Industrial economy